Bioengineered in vitro models of thrombosis: methods and techniques - Zhang, Yu Shrike; Oklu, Rahmi; Albadawi, Hassan (Cardiovascular Diagnosis and Therapy, 2017)
Thrombosis is a prevailing vascular disorder that has been historically studied in vivo with conventional animal models. Here we review recent advances in methods and techniques that allow for engineering of biomimetic in vitro models of thrombosis, usually combined with micro uidic devices, termed thrombosis-on-a-chip systems, to reproduce such vascular pathology outside living organisms. These human cell-based thrombosis-on-a-chip platforms recapitulate the important characteristics of native thrombosis in terms of vascular structures, extracellular matrix properties, cellular composition, and pathophysiology, making them enabling in vitro models to study this important class of vascular disorders as well as to develop personalized treatment regimens.